Ulcerative colitis: Impact of early disease clearance on long‐term outcomes ‐ A multicenter cohort study. Issue 7 (15th September 2022) - D'Amico, Ferdinando; Fiorino, Gionata; Solitano, Virginia; Massarini, Eugenia; Guillo, Lucas; Allocca, Mariangela; Furfaro, Federica; Zilli, Alessandra; Bonovas, Stefanos; Magro, Fernando; Peyrin‐Biroulet, Laurent; Danese, Silvio
Abstract: Background: Clinical remission and endoscopic mucosal healing are the main treatment targets in patients with ulcerative colitis (UC). Recently, the concept of disease clearance has been proposed as a potential target in UC. Objective: We aimed to evaluate the impact of disease clearance on long‐term outcomes in UC patients. Methods: A multicenter retrospective cohort study was conducted at the Humanitas Research Hospital‐IRCCS (Italy) and at the Nancy University Hospital (France) between 2014 and 2021. Disease clearance in UC was defined as simultaneous clinical (partial‐Mayo score ≤2), endoscopic (endoscopic‐Mayo score = 0), and histological (Nancy index = 0) remission, and patients were monitored over a long‐time follow‐up (≥12 months), to compare the occurrence of negative outcomes. Results: A total of 494 patients with UC was included in the study (269, 54.4% males). Disease clearance was present in 109 patients (22.1%) at baseline. Median follow up was 24 months. Patients with disease clearance were associated to a significantly lower risk of UC‐related hospitalization compared with the control group (5.5% vs. 23.1%; p < 0.001) at last observation. Similarly, a lower rate of surgeries was detected in patients with disease clearance at baseline compared with those without (1.8% vs. 10.9%; p = 0.003). The Kaplan Meier curves confirmed that patients with disease clearance at baseline had a lower risk of hospitalization (log‐rank p < 0.0001) and surgery (log‐rank p < 0.00095). Conclusion: In UC patients with early disease clearance are at significant lower risk for hospitalization and surgery. Disease clearance should be considered as a new composite outcome.